Early Childhood Longitudinal Study (United States): Kindergarten Class of 1998-1999 ([Verlag nicht ermittelbar], 2003)
The Early Childhood Longitudinal Study (ECLS) program provides national data on children's status at birth and at various points thereafter, children's transition to nonparental care, early education programs, and school, and children's experiences and growth through the fifth grade. ECLS also provides data to test hypotheses about the effects of a wide range of family, school, community, and individual variables on children's development, early learning, and early performance in school. The Kindergarten Class of 1998-1999 addresses four key issues: (1) school readiness, (2) children's transitions to kindergarten, first grade, and beyond, (3) the relationship between children's kindergarten experience and their elementary school performance, and (4) children's growth in math, reading, and general knowledge (i.e., science and social studies), and their progress through elementary school.